2015
DOI: 10.1083/jcb.201408017
|View full text |Cite
|
Sign up to set email alerts
|

Excision of translesion synthesis errors orchestrates responses to helix-distorting DNA lesions

Abstract: An Msh2/Msh6-dependent DNA repair mechanism mitigates the mutagenicity of photolesions and induces cell cycle responses by excising incorrect nucleotides incorporated by postreplicative translesion synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…In this pathway, MutSα targets mismatches formed by TLS opposite (6-4)PP lesions thereby acting downstream of NER and TLS [126]. The presence of long-lived excision intermediates consisting of gapped DNA coated with RPA serves as a signal for ATR kinase and will give rise to broken chromosomes upon replication in the next cell cycle.…”
Section: Oxidative Damage and Dna Adductsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this pathway, MutSα targets mismatches formed by TLS opposite (6-4)PP lesions thereby acting downstream of NER and TLS [126]. The presence of long-lived excision intermediates consisting of gapped DNA coated with RPA serves as a signal for ATR kinase and will give rise to broken chromosomes upon replication in the next cell cycle.…”
Section: Oxidative Damage and Dna Adductsmentioning
confidence: 99%
“…In the case of Lynch syndrome colorectal cancer, the rate of cellular proliferation is surely an important contributor, but it is unlikely to be the only factor. Tsaalbi-Shtylik et al suggest that the loss of post-TLS repair and attendant elevated mutagenesis leads to disruption of multiple tumor suppressing functions, and in combination with constant exposure to intestinal genotoxins, may explain the colorectal tropism of Lynch syndrome [126]. …”
Section: Oxidative Damage and Dna Adductsmentioning
confidence: 99%
“…Consistent with their role in surveying the replication products of Pol IV, the ϵ exonuclease and Pol II affect several Pol IV-dependent mutagenic phenomena ( 9 , 56 ). In addition, it has been demonstrated that the eukaryotic heterodimer Msh2/Msh6 suppress UV-induced mutagenesis by mediating the excision of incorrect nucleotides introduced by error-prone TLS Pols ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of ES cells derived from mice harboring defects in NER and/or MMR and exposed to short wavelength UVC irradiation suggests a novel "post-TLS" repair pathway in proliferating cells for MMR-dependent, UV-induced mutagenesis and DNA damage signaling. In this pathway, MutSα targets mismatches formed by TLS opposite (6-4)PP lesions thereby acting downstream of NER and TLS [126]. The presence of long-lived excision intermediates consisting of gapped DNA coated with RPA serves as a signal for ATR kinase and will give rise to broken chromosomes upon replication in the next cell cycle.…”
Section: Oxidative Damage and Dna Adductsmentioning
confidence: 99%